Analisis Perkembangan Pariwisata di Kawasan Pesisir Pantai Holtekamp Kota Jayapura Sebagai Dampak Pembangunan Jembatan Youtefa - Samuel Kambu; Irja Tobawan Simbiak; Sudiro Sudiro (Fakultas Teknik Universitas Cenderawasih, 2024)
With the potential for various economic impacts in the Holtekamp Coastal Area due to the construction of the Youtefa Bridge, it is necessary to analyze the multiplier effects in the Holtekamp Coastal Area. In this study, the researcher used a combination of qualitative and quantitative research methods called a mixed research method. In this method, the researcher simultaneously collects qualitative and quantitative data sourced from questionnaires, observations, and document studies. The data analysis methods used in this study include the Likert Scale, descriptive analysis, and multiplier effect analysis. The results of this study indicate that the overall perception of the community, both business actors, local workers, and tourists, towards every tourism condition in Holtekamp Beach is ranked Moderate to Very Good. However, several aspects still need to be considered, including street lighting, less than optimal, and the availability of souvenirs, which still needs to be improved. Overall, the Holtekamp Beach tourist area has had a considerable impact, which can be seen from the results of the multiplier value calculations, which show a value greater than one (>1), including the Keynesian Income Multiplier value of 1.51, the Ratio Income Multiplier type I value of 1.66 and the Ratio Income Multiplier type II value of 1.80.